Ingroup relationships of Lagerpetidae (Avemetatarsalia: Dinosauromorpha): a further phylogenetic investigation on the understanding of dinosaur relatives - Müller, Rodrigo Temp; Langer, Max Cardoso; Dias-Da-Silva, Sérgio (Zootaxa, 2018)
Despite representing a key-taxon in dinosauromorph phylogeny, Lagerpertidae is one of the most obscure and enigmatic branches from the stem that leads to the dinosaurs. Recent new findings have greatly increased our knowledge about lagerpetids, but no phylogenetic analysis has so far included all known members of this group. Here, we present the most inclusive phylogenetic study so far conducted for Lagerpetidae. Phylogenetic analyses were performed based on three independent data matrixes. In two of them, Lagerpeton chanarensis Romer, 1971 is the sister taxon to all other known Lagerpetidae, whereas Ixalerpeton polesinensis Cabreira et al., 2016 is in a sister group relationship with a clade that includes PVSJ 883 and Dromomeron. Conversely, the other analysis supports an alternative topology, where I. polesinensis is the sister taxon to either L. chanarensis or all other Lagerpetidae. Although coeval and geographically close, I. polesinensis and PVSJ 883 do not form a clade exclusive of other lagerpetids. As previously suggested D. gigas Martínez, Apaldetti, Correa & Abelín, 2016 is the sister taxon of D. romeri Irmis et al., 2007. The phylogenetic analyses also indicate that the earliest lagerpetids are restricted to southwestern Pangea, whereas later forms spread across the entire western portion of the supercontinent. Finally, quantification of the codified characters of our analysis reveals that Lagerpetidae is one of the poorest known among the Triassic dinosauromorph groups in terms of their anatomy, so that new discoveries of more complete specimens are awaited to establish a more robust phylogeny.